1997
DOI: 10.1176/ajp.154.2.218
|View full text |Cite
|
Sign up to set email alerts
|

High levels of Gs alpha in platelets of euthymic patients with bipolar affective disorder

Abstract: Objective: Previous investigations have suggested the involvement of signal-transducing guanine-nucleotide-binding proteins (G proteins) That lithium, a single inorganic ion, can reverse a major psychotic reaction must have, quite apart from its substantial therapeutic value, profound theoretical significance in unraveling the mystery of the so-called functional psychoses. It must be regarded as a major research tool.Cade (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The G protein-bound adenylate cyclase catalyzes the conversion of ATP into c-AMP, which activates PKA, which in turn regulates several intracellular processes including phosphorylation of CREB, a transcription factor [136]. Increased c-AMP signaling is also implicated in BD [137,138,139]. In vivo microdialysis revealed that direct activation of PKC by PMA in the frontal cortex and hippocampus increases c-AMP in the dialysate [39].…”
Section: Downstream Targets Of Pkcmentioning
confidence: 99%
“…The G protein-bound adenylate cyclase catalyzes the conversion of ATP into c-AMP, which activates PKA, which in turn regulates several intracellular processes including phosphorylation of CREB, a transcription factor [136]. Increased c-AMP signaling is also implicated in BD [137,138,139]. In vivo microdialysis revealed that direct activation of PKC by PMA in the frontal cortex and hippocampus increases c-AMP in the dialysate [39].…”
Section: Downstream Targets Of Pkcmentioning
confidence: 99%
“…Several studies have shown that mRNA levels for Gαs, the stimulatory G-protein that couples with AC, are increased in peripheral cells of BPD patients. 30, 31, 32, 33, 34 Post-mortem analyses on brain have demonstrated an increased abundance of the Gαs protein, but not Gαi or Gαo, 32, 30 and lithium has been found to decrease the abundance of mRNAs for several G-proteins. 35, 36 Lithium may also decrease the coupling of receptors to G-proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in G proteins coupled to cAMP signaling have also been reported in patients with bipolar disorder [ 34 , 39 , 40 , 41 , 42 , 43 , 44 ] and may potentially lead to dysfunctions of the downstream components of the cAMP dependent phosphorylation such as PKA and Rap1.…”
Section: G Proteins and Adenylyl Cyclase-camp And Their Role In Dementioning
confidence: 99%